Reformulation markers of distancing in Spanish: sociolinguistic and geolectal patterns - San Martín Núñez, Abelardo; Rojas Inostroza, Cristian (Círculo de Lingüística Aplicada a la Comunicación, 2023)
In this article, we approach the geolectal and sociolinguistic variation of a specific type of discursive marker in Spanish, namely, distancing reformulators, which are units of pragmatic functioning through which the speakers reformulate what they have said to distance themselves from a previous statement. Our general aim is to analyze the use of the most frequent distancing reformulation markers in different geographical varieties of Spanish, both in Spain and in America, using samples from the corpus of the Project for the sociolinguistic study of Spanish in Spain and America (PRESEEA). This way, we determine the existence of distancing reformulators of more general or pan-Hispanic use and others of more particular or idiosyncratic use in each speech community from a geolectal and sociolinguistic variationist approach.